(3OQGSI ebGQfI aj GdJTQjY GdeUQj hGdYQHj hGdaQfSjs - (3eLOj eMH(B, (3MGaXs ([(3O(B.(3e(B]:s [ (3O(B.(3f(B],s, 2002)
(3ebOeI Mhd GdTjc(B- (3GdWHjYI GdbGfhfjI ddTjc(B- (3JOGhd GdTjc(B- (3GdhaGA HGdTjc(B- (3CfhGY NGUI ef GdTjcGJ(B- (3CQcGf LQGFe GdTjc(B- (3YbhHI EYWGA Tjc HOhf QUjO(B- (3GdeMGceI aj LQGFe GdTjcs
Keywords: (3GdTjcGJs; (3LQGFe GdGNJdGSs